Motivational development and learning success in regular semesters and distance semesters under pandemic conditions in an educational psychology lecture course - Sander, Zoe; Bosch, Eva; Spinath, Birgit (The journal of experimental education, 2024)
This study compared university students’ motivational development and learning success during multiple regular and pandemic distance semesters. In general, a decline in expectancies and task values was expected during semesters. Based on situated expectancy-value theory, we exploratively examined how situative pandemic-related factors were related to motivational development, knowledge acquisition, and ceased self-testing. Data from N = 690 students attending the same lecture course on educational psychology were assessed in four regular (n = 426) and three distance (n = 264) semesters using latent growth curve modeling. Declines in all motivational components except attainment value were found in the overall sample. Motivation did not differ between regular and distance semesters. However, regarding learning success, students in pandemic distance semesters showed lower knowledge test performance and ceased self-testing more often and earlier. There were many concerns that the pandemic had a strong negative impact on students’ motivation and learning success. However, our results provide evidence that students’ motivation was quite robust. Nonetheless, the high rate of ceased self-testing in distance semesters is a concerning result and our study highlights the need for strategies to provide increased support for learners under regular as well as special conditions.
Online veröffentlicht: 18. April 2024
Gesehen am 16.08.2024 (nur frontdoor)